2000
DOI: 10.1021/es001033h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acid Volatile Sulfide and Metal Concentrations on Metal Bioavailability to Marine Invertebrates in Contaminated Sediments

Abstract: An 18-day microcosm study was conducted to evaluate the influence of acid volatile sulfides (AVS) and metal additions on bioaccumulation from sediments of Cd, Ni, and Zn in two clams (Macoma balthica and Potamocorbula amurensis) and three marine polychaetes (Neanthes arenaceodentata, Heteromastus filiformis, and Spiophanes missionensis). Manipulation of AVS by oxidation of naturally anoxic sediments allowed use of metal concentrations typical of nature and evaluation of processes important to chronic metal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 65 publications
5
63
0
5
Order By: Relevance
“…Therefore applying this theory to metal remobilization studies would be proper only in the case that sulfides are not oxidized during elutriation (Di Toro et al, 1990;Durán et al, 2012). During the past years, much evidence has shown that benthic invertebrates can accumulate metals, even when [SEM]-[AVS] < 0, since benthic invertebrates ingest sediment particles as their main food source disregarding AVS (Lee et al, 2000a;Lee et al, 2000b;De Jonge et al, 2009;De Jonge et al, 2010). YHH3 YHH2 YHH1 GLH3 GLH2 GLH1 YHH-GLH ZMH2 ZMH1 ZM-YHH L1 L2 L3 L4 L5 MH6 MH5 XQH4 XQH3 XQH2 XQH1 K1 K2 K3 MH4 MH3 MH2 MH1 J1 J2 J3 J4 BLH3 BLH2 BLH1 I1 I2 I3 DH2 DH1 YH5 YH4 YH3 YH2 YH1 H1 H2 H3 WH3 WH2 WH1 JLH2 SEMs can be combined with AVS to reduce their toxicity; however, AVS of excessively high content is also harmful to aquatic organism.…”
Section: The Limitations Of Avs-sem Evaluation Methodsmentioning
confidence: 99%
“…Therefore applying this theory to metal remobilization studies would be proper only in the case that sulfides are not oxidized during elutriation (Di Toro et al, 1990;Durán et al, 2012). During the past years, much evidence has shown that benthic invertebrates can accumulate metals, even when [SEM]-[AVS] < 0, since benthic invertebrates ingest sediment particles as their main food source disregarding AVS (Lee et al, 2000a;Lee et al, 2000b;De Jonge et al, 2009;De Jonge et al, 2010). YHH3 YHH2 YHH1 GLH3 GLH2 GLH1 YHH-GLH ZMH2 ZMH1 ZM-YHH L1 L2 L3 L4 L5 MH6 MH5 XQH4 XQH3 XQH2 XQH1 K1 K2 K3 MH4 MH3 MH2 MH1 J1 J2 J3 J4 BLH3 BLH2 BLH1 I1 I2 I3 DH2 DH1 YH5 YH4 YH3 YH2 YH1 H1 H2 H3 WH3 WH2 WH1 JLH2 SEMs can be combined with AVS to reduce their toxicity; however, AVS of excessively high content is also harmful to aquatic organism.…”
Section: The Limitations Of Avs-sem Evaluation Methodsmentioning
confidence: 99%
“…Isto porque a biodisponibilidade de metais não é necessariamente indicativa de toxicidade, pois condições ecológicas e fisiológicas podem modificar a extensão em que os organismos são expostos aos metais (Lee et al 2000).…”
Section: Methodsunclassified
“…The sediment samples were handled under a glove bag filled with N 2 gas. In the laboratory, a portion of the collected sediment was spiked with metals and manipulated for appropriate AVS levels following a protocol established by Lee et al (2000b). Briefly, the sediment was mixed with the equal volume of deoxygenated seawater (30 psu) that had been previously spiked with the metal stock solutions prepared with reagent grade AgNO 3 , CdCl 2 and ZnCl 2 .…”
Section: Methodsmentioning
confidence: 99%